Социальная эксклюзия в Украине на начальной стадии реставрации капитализма - Оксамитная, С.; Хмелько, В. (Социология: теория, методы, маркетинг, 2004)
Data of 18 surveys based on random samples representative for adult population of Ukraine from 18 years old conducted by the Kyiv International Institute of Sociology within the period from 1991 to 2003 by the method of face-to-face interview are analysed. Dynamics of five indicators of the social exclusion are considered: long unemployment (during one year or more); lack of the compulsory school education at adults from 18 to 40 years of age; absence of any help from individual’s associates when an individual was in need of some help; belonging to household having an income per person less by half of median one in the corresponding region; belonging to household having a lack of means for daily food.